2023
DOI: 10.3390/ijerph20054215
|View full text |Cite
|
Sign up to set email alerts
|

Text4PTSI: A Promising Supportive Text Messaging Program to Mitigate Psychological Symptoms in Public Safety Personnel

Abstract: Background: Public safety personnel experience various mental health conditions due to their work’s complex and demanding nature. There are barriers to seeking support and treatment; hence, providing innovative and cost-effective interventions can help improve mental health symptoms in public safety personnel. Objective: The study aimed to evaluate the impact of Text4PTSI on depression, anxiety, trauma, and stress-related symptoms, and the resilience of public safety personnel after six months of providing sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Additionally, PSP often work long and irregular hours, making it challenging to maintain a healthy lifestyle and work-life balance. Another source of stress for PSP may include the culture of their organizations [ 6 ]. Many public safety agencies have a culture of stoicism and toughness, which can discourage employees from seeking help for mental health problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PSP often work long and irregular hours, making it challenging to maintain a healthy lifestyle and work-life balance. Another source of stress for PSP may include the culture of their organizations [ 6 ]. Many public safety agencies have a culture of stoicism and toughness, which can discourage employees from seeking help for mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…When supportive intervention is provided, most studies have demonstrated a decrease in mental health symptoms. For example, in a longitudinal study to assess the effectiveness of an SMS text message intervention, PSP who subscribed to the texting program reported that they were able to manage depression, anxiety, and other psychological symptoms [ 6 ]. Similarly, 10 randomized controlled trials providing therapeutic intervention through texting demonstrated a substantial improvement in psychological symptoms compared to conventional treatment [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another related service, the Text4Hope-Addiction program, was introduced to people living with substance use disorders; the service reported significant improvement in standardized measures for craving, anxiety, and depression in subscribers [ 45 ]. Similarly, the Text4PTSI program significantly reduced psychological distress among public safety personnel postintervention [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMS text messaging services such as Text4Support effectively reduced the risk of harm to self and other harm symptoms after 6 months of intervention in a randomized controlled trial [ 23 ] and improved distress, anxiety, and depression in clinical samples [ 24 ]. Similarly, the Text4PTSI program has achieved fidelity and significantly reduced psychological distress among public safety personnel post intervention [ 25 , 26 ]. SMS text message–based population-level messaging programs have reported user satisfaction rates of well over 80%, and most subscribers have reported feeling connected to support systems and improving their ability to manage anxiety, depression, and general life issues, suggesting an improvement in mental health literacy [ 15 , 27 - 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the psychological impact of wildfires, developing effective support and intervention strategies is essential to mitigate the long-term psychological impact on affected populations. Innovative, cost-efficient, technologically enabled, and easily scalable interventions, such as daily supportive SMS text messaging [14][15][16][17], may hold the key to the provision of support to impacted communities during and after wildfires. While the use of text messaging as an intervention in mental health has been explored in various contexts, its application in a wildfire-impacted population is a novel area for research [1,18].…”
Section: Introductionmentioning
confidence: 99%